1988
DOI: 10.1002/1097-0142(19880315)61:6<1167::aid-cncr2820610618>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum neuron-specific enolase in patients with malignant pheochromocytoma

Abstract: Neuron-specific enolase (NSE), an isomer of glycolytic enzyme enolase, is found exclusively in neuroendocrine cells and in neuroendocrine tumors in a considerably large quantity. Circulating levels of serum NSE were measured by radioimmunoassay in 24 normal adults, 23 patients with benign pheochromocytoma, three patients with malignant pheochromocytoma, and seven patients with medullary thyroid carcinoma. The mean serum NSE in normal adults was 5.8 +/- 1.3 ng/ml (mean +/- standard deviation [SD], and the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 16 publications
1
11
1
1
Order By: Relevance
“…It is a widely used immunohistochemical and serum marker for neuroendocrine tissues and is especially known as a marker for small cell lung carcinoma (26). Our data confirm the frequent elevation of its serum concentrations in patients with several neuroendocrine tumors (27)(28)(29). The highest levels were encountered in small cell lung carcinoma and in the rare cases of Merkel cell tumors.…”
Section: Discussionsupporting
confidence: 86%
“…It is a widely used immunohistochemical and serum marker for neuroendocrine tissues and is especially known as a marker for small cell lung carcinoma (26). Our data confirm the frequent elevation of its serum concentrations in patients with several neuroendocrine tumors (27)(28)(29). The highest levels were encountered in small cell lung carcinoma and in the rare cases of Merkel cell tumors.…”
Section: Discussionsupporting
confidence: 86%
“…Secretogranin II and prohormone convertases 1 and 2 were found to be overexpressed in benign when compared with malignant tumours (Guillemot et al 2006). Neuron-specific enolase has also been advocated as a screening marker since it can be significantly elevated in patients with malignant phaeochromocytomas (Oishi & Sato 1988). Of the several other peptides that can be produced from chromaffin-cell tumours, adrenocorticotrophin over-expression has been related to malignancy (Moreno et al 1999).…”
Section: Biochemical Diagnosis Of Malignant Chromaffin-cell Tumoursmentioning
confidence: 99%
“…In accordance, chromogranin A has been used to monitor patients during chemotherapy of malignant PCCs [55]. Some investigators have reported a high serum concentration of neuron-specific enolase (NSE) [56].…”
Section: Unspecific Biomarkersmentioning
confidence: 99%